(3Pjd WHbGJ GdMfGHdIs - (3YHO GdQMef Hf CMeO Hf QLH GdMfHdj GdqSdGej GdHZOGOj Ke GdOeTbqj, CHh GdaQL, Rjf GdOjf,J (B795 (3g` s; (3eMeO Hf eMeO GdbGVj GdaQGA GdMfHdj, CHj jYdj,J (B526 (3g` s ((3EdjGS Hf NVQ Hf eMeO Hf LHQGFjd GdJQceGfi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf (B,(3JHOC HJQLeI YHO GdNGdb Hf YjSi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B159 - (3U(B351s
(3fSNI QGHYis
(3jdjgG (B: (3QSGdI ai eYfi GdYde hEfbSGeg ai (B6 (3hQbGJs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B23s
Keywords: (3GdJGQjNs